Partition of energy in diving - Stroup, F. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
Although I realize that time is at a premium, I would be negligent indeed if I did not take a ~oment to express my gratitude for the opportunity to participate in this seminar and my delight in exchaning ideas with students of international eminence on subjects that have been of interest to me for nearly half a century. And of the subjects to be discussed here, the one that, through the years, has presented the greatest personal challenge to me - the one that has aroused my abiding curiosity - has been the cause of rotation around the frontal axis of the body in a diving performance. In fact, my concern with this subject has been so consistent for so long that my presentation today may sound more like an autobiography than a research report.